KECERDASAN INTERPERSONAL MAHASISWA PENDIDIKAN LUAR SEKOLAH FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS RIAU TAHUN PELAJARAN 2019 - Rikha rofiatul afiyah; Wilson Wilson; Daeng ayub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: How high is the interpersonal intelligence of extracurricular students at the University of Riau Education and Teaching Faculty in the academic year 2019, how are the aspects of the interpersonal intelligence of the external teaching faculty of the teacher school and the teaching of the University of Riau in the academic year 2019. This research is descriptive with a quantitative approach. The population in this study was 144 people. Sampling in this study using simple samples. The instrument used is a questionnaire with 66 item statements. Interpersonal intelligence Extracurricular education Students Education and training Faculty Riau University Academic year 2019 is measured by indicators (1) Social insight, (2) social sensitivity, (3) social communication. The results of the study reveal that (1) Interpersonal levels of intelligence of extracurricular students of the University of Riau Teacher Training and Education of the Academic Year 2019 have a moderate interpretation. (2) The aspect that makes the greatest contribution to interpersonal intelligence is the number 1 aspect, namely social insight with a comparison with the score (88.70%) that is classified as high of the other aspects.Key Words: Interpersonal Intelligence, Students